Extract from Fructus cannabis activating calcineurin improved learning and memory in mice with chemical drug-induced dysmnesia - Luo Jing; Yin Jiang-Hua; Wu He-Zhen; Wei Qun (Acta Pharmacologica Sinica; Vol 24, No 11 (November 2003): Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effects of extract from Fructus cannabis (EFC) that can activate calcineurin on learning and memory impairment induced by chemical drugs in mice. METHODS: Bovine brain calcineurin and calmodulin were isolated from frozen tissues. The activity of calcineurin was assayed using p-nitrophenyl phosphate (PNPP) as the substrate. Step-down type passive avoidance test and water maze were used together to determine the effects of EFC on learning and memory dysfunction. RESULTS: EFC activated calcineurin activity at a concentration range of 0.01-100 g/L. The maximal value of EFC on calcineurin activity (35 %+/-5 %) appeared at a concentration of 10 g/L. The chemical drugs such as scopolamine, sodium nitrite, and 45 % ethanol, and sodium pentobarbital induced learning and memory dysfunction. EFC administration (0.2, 0.4, and 0.8 g/kg, igx7 d) prolonged the latency and decreased the number of errors in the step-down test. EFC, given for 7 d, enhanced the spatial resolution of amnesic mice in water maze test. EFC overcome amnesia of three stages of memory process at the dose of 0.2 g/kg. CONCLUSION: EFC with an activation role of calcineurin can improve the impaired learning and memory induced by chemical drugs in mice.